(3GdcdjGJs - (3eMeO Hf CMeO Hf eMeO Hf QTO GdbQWHj GdCfOdSj, CHh GdhdjO (B((3GdMajO(B)(3,J (B595 (3g` s
(3ChdgG (B:s
(3Ef gPg GdUfGFY HYVgG fXQi hgj GdYde GdWHjYi hHYVgG Yedi s
(3BNQgG (B:s
(3hajg GdNhGU Ydi hLhH GdfXQ GdJGe ai CUd GdTQjYI hGddg Gdehab hGdgGOi HaVdg hfYeJg ced GdcJGH hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B318 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B313s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdWHs